Book review: Disability studies: Emerging Insights and Perspectives (Concept: The Journal of Contemporary Community Education Practice Theory, 2011)
Book review: Disability studies: Emerging Insights and Perspectives Edited by: Thomas Campbell, Fernando Fontes, Laura Hemingway, Armineh Soorenian and Chris TillThe Disability Press, Leeds. 2008.